Copper Toxicity and Tolerance in Plants: Insights from Omics Studies - Moreira, A.; Moraes, L. A.C.; Delfim, J. J.; Moreti, L. G. [UNESP] (Wiley, 2023)
Copper (Cu) is an essential micronutrient, whose deficiency, tolerance, and excess in plants have been widely reported in many regions of the world. Cu utilization efficiency (CuUE) is essential for food crops and human health. Copper uptake and CuUE in plants is complex, as each step, including root and foliar uptake, assimilation, translocation, and remobilization, is governed by multiple interacting environmental and genetic factors. Copper transportation from roots to shoots occurs through the xylem, followed by easy translocation by the phloem. The Cu uptake into cells and its movement into and out of intracellular organelles require specific proteins, generally known as transporter proteins that span cell membranes. Advancement in molecular biology techniques allows the interpretation of the complexity and variations in the processes involved in the toxicity and tolerance of plant tissues to excess Cu in the environment at several levels, such as the genomic, transcriptomic, proteomic, miRNAomic, and metabolomic. Here, the interactions between multiple genes, RNAs, proteins, and the environment have been critically reviewed to provide a clear understanding of the Cu-related processes and mechanisms in plants.